Branching patterns of olivocerebellar axons in relation to the compartmental organization of the cerebellum - Fujita, Hirofumi; Sugihara, Izumi (Frontiers in Neural Circuits, 2013)
A single olivocerebellar (OC) axon gives rise to about seven branches that terminate as climbing fibers (CFs). Branching patterns of an OC axon, which are classified into local, transverse and longitudinal types, are highly organized, in relation to the longitudinal molecular (aldolase C or zebrin II) compartmentalization and the transverse lobulation of the cerebellum. Local branching is involved in forming a narrow band-shaped functional subarea within a molecular compartment. On the other hand, transverse and longitudinal branchings appear to be involved in linking mediolaterally separated molecular compartments and rostrocaudally separated lobular areas, respectively. Longitudinal branching occurs frequently between equivalent molecular compartments of specific combinations of lobules. These combinations include lobule V-simple lobule and crus II-paramedian lobule in the pars intermedia and hemisphere, and lobules I-V and lobule VIII in the vermis. The longitudinal branching pattern not only fits with mirror-imaged somatosensory double representation of the body in the pars intermedia, but it also suggests a general rostrocaudal link exists for the whole cerebellum across the putative rostrocaudal boundary in lobule VIc-crus I. Molecular compartments of the cerebellar cortex originate from the Purkinje cell (PC) clusters that appear in the late embryonic stage, when the immature OC projection is formed. Some clusters split rostrocaudally across crus I during the development of cortical compartments, which would result in longitudinal branching of OC projection across crus I. Supposing that the branching pattern of OC axons represents an essential organization of the cerebellum, longitudinal branching suggests a functional and developmental links between the rostral and caudal cerebellum across lobule VIc-crus I throughout the cerebellar cortex.